Authenticity at Work: Its Relations With Worker Motivation and Well-being - Van den Bosch, Ralph; Taris, Toon (Frontiers in Communication, 2018)
Drawing on Self-Determination Theory (Deci, Olafsen & Ryan, 2017), this study examines the associations between authenticity at work, motivation and well-being, assuming that motivation would at least partly mediate the association between authenticty and well-being. Since authentic behavior refers to the degree to which a person acts in agreement with their true self (i.e., one's own core values), high levels of authenticity at work should relate positively to more intrinsic types of motivation regulation and negatively to more extrinsic types of motivation regulation. Moreover, high levels of authenticity should be associated with higher well-being at work (i.e., higher work engagement and lower burnout). Structural equation modeling using cross-sectional data from 546 participants revealed that self-determined motivation (i.e. autonomous motivation) showed positive associations with authenticity at work and that non-self-determined motivation (i.e. controlled motivation and amotivation) showed negative associations with authenticity at work. The positive associations increased in strength with increasing self-determined motivation. A similar – but reversed – pattern was found for the negative associations. Parallel mediation analysis revealed that self-determined motivation partially mediated the relationship between authenticity and well-being at work.